Uterine perforation following a fractional curettage successfully treated with the modified polysaccharide 4DryField® PH: a case report. (December 2016) - Ziegler, Nicole; Korell, Matthias; Herrmann, Anja; de Wilde, Maya; Torres-de la Roche, Luz; Larbig, Angelika; De Wilde, Rudy
Abstract Background Uterine perforation is the most common complication of curettage and may result in bleeding. Therefore, urgent control of bleeding from the uterine wall perforation is necessary to avoid an emergency hysterectomy or blood transfusion, to prevent peritoneal adhesion formation, possible chronic pelvic pain, and infertility. In the present case, an active bleeding secondary to a perforation of the uterus during curettage, for diagnosis of endometrial carcinoma, was instantaneously and successfully treated with only the application of a novel modified polysaccharide powder. This is, to the best of our knowledge, the first time that the agent 4DryField® has been used for this purpose. Case presentation A 71-year-old German woman with serometra and endometrial hyperplasia suffered a perforation of the anterior wall of the uterus during the hysteroscopic resection of submucosal polyps and a fractional curettage. Subsequently, an immediate laparoscopy showed an active bleeding from the wound, which was promptly stopped with only the application of the hemostatic and anti-adhesion polysaccharide powder, 4DryField®. There were no postoperative complications. Nine weeks later, a laparoscopic hysterectomy with bilateral salpingoophorectomy for endometrial carcinoma (histology: stage IA, pT1a, cN0, L0 V0 M0/G2) was performed. The former injured area looked slightly prominent, was completely healed, and showed a shiny serosa. All her pelvic organs were free of adhesions, and there was one 0.5-mm calcified granuloma in the Douglas pouch. Conclusions The efficient hemostasis combined with the adhesion prevention effect of 4DryField®, allowed a fast control of the uterine wall bleeding, saved operation time, avoided the risks of other procedures for bleeding control and contributed to the normal healing of the uterine wall without any adhesion formation.